Gambaran dinamika psikologis dan konsep diri remaja yang sering mengalami kerauhan - Wisnawa, Gede Adi; Fridari, I Gusti Ayu Diah (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2021)
Bali is full of rituals and ceremonies in every activity that exists. Kerauhan is a phenomenon that is very close to the Balinese Hindu community. Unfortunately, people often only associate this phenomenon with negative things such as being possessed by a demon or wandering spirits. In a different view, this phenomenon is believed to be a symbol of God's presence. This causes kerauhan to become increasingly complex for the public to understand. Kerauhan experienced by a person has a psychological impact on their life. The perceived impact affects the individual's self-concept, namely how certain beliefs, views, attitudes, and evaluations an individual has of them self. This research aims to describe the psychological dynamics and self-concept of adolescents who often experienced kerauhan. This research uses a qualitative method with a multicase study approach. The sampling technique used was purposive sampling technique. The respondents for this research are 3 women and 2 men who were in the adolescent phase and often experienced kerauhan in Hindu religious ceremonies in Bali. Collecting data using a semi-structured interview method. Meanwhile, the data analysis used in this research is thematic analysis. The results showed that most respondents accepted the experience of kerauhan because they thought that kerauhan was a gift from God, the respondents had a good understanding of what they wanted to be and the social role they played, and all respondents had a tendency to have positive self-concept.